2021
DOI: 10.1177/0269881121998321
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative and quantitative account of patient’s experiences of ketamine and its antidepressant properties

Abstract: Background: Ketamine is central to one of the most rapidly growing areas of neuroscientific research into novel treatments for depression. Limited research has indicated that the psychedelic properties of ketamine may play a role in its antidepressant effects. Aim: The aim of the current study was to explore the psychedelic experiences and sustained impact of ketamine in major depressive disorder. Methods: In the current study, ketamine (0.44 mg/kg) was administered to 32 volunteers with major depressive disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 74 publications
4
38
0
1
Order By: Relevance
“…These psychedelic effects are usually either not addressed (Grabski et al, 2020;Mathai et al, 2020) or regarded as unwanted 'psychotic' side adverse effects in clinical trials (Romeo et al, 2015). In contrast, it has also been suggested that ketamine-induced psychedelic peak experiences may contribute to its antidepressant effect (Sumner et al, 2021). Interestingly, studies that administered ketamine to anesthetized patients-thereby canceling out acute psychedelic effects-reported short-term effects on depression, indicating that the psychedelic experience is not necessary for its effect on depression.…”
Section: Discussionmentioning
confidence: 99%
“…These psychedelic effects are usually either not addressed (Grabski et al, 2020;Mathai et al, 2020) or regarded as unwanted 'psychotic' side adverse effects in clinical trials (Romeo et al, 2015). In contrast, it has also been suggested that ketamine-induced psychedelic peak experiences may contribute to its antidepressant effect (Sumner et al, 2021). Interestingly, studies that administered ketamine to anesthetized patients-thereby canceling out acute psychedelic effects-reported short-term effects on depression, indicating that the psychedelic experience is not necessary for its effect on depression.…”
Section: Discussionmentioning
confidence: 99%
“…Rachael Sumner and colleagues conducted qualitative interviews looking at the psychedelic experiences and sustained impact of ketamine in patients with major depressive disorder (MDD). This study provided preliminary evidence for the role of the psychedelic experience and afterglow in ketamine's antidepressant properties (Sumner et al, 2021). Furthermore, there may be a rationale for psychotherapeutic guidance as part of ketamine therapy for MDD, as well as greater attention to the context in which ketamine is administered.…”
mentioning
confidence: 77%
“…In a subsequent study where participants with heroin use disorders were randomised to receive either a "psychedelic" dose of ketamine [2.0 mg/kg Intramuscular (IM)] or a "sub-psychedelic" dose (0.2 mg/kg IM), the rate of abstinence over 2 years was higher in the former group than the latter (14) indicating a therapeutic benefit of ketamine-induced psychedelic experiences. Additionally, in a recent report antidepressant response was correlated with dimensions of altered states of consciousness such as feelings of unity, spirituality and insight (15). Moreover, ketamine's therapeutic effects on motivation to quit cocaine and cocaine use were mediated by ketamine's mystical type effects-but not dissociative effects (16,17).…”
Section: Introductionmentioning
confidence: 92%